1993
DOI: 10.1021/ja00072a020
|View full text |Cite
|
Sign up to set email alerts
|

Methyl transfers. 15. CoIPc- as a nucleophile and leaving group

Abstract: Many complexes of cobalt in the + 1 oxidation state are excellent nucleophiles. The complex with phthalocyanine, Pcz-, is an example; the rates of reaction of complex (CdPc)-, 1-, with Me1 and other alkylating agents in dimethylacetamide (DMA) solution are reported. In contrast to previous studies with other Co(1) complexes, the rate of reaction of the methylated product, (MeCoII'Pc, 3) with I-is also readily measured, allowing a kinetic evaluation of the equilibriumSimilarly, B r also reacts with 3 reversibly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 0 publications
2
27
0
Order By: Relevance
“…The activation enthalpies for the methyl system are at least 6 kcal/mol higher than those determined for S N 2 methyl transfers from CH 3 CoPc, while the activation entropies for the two reactions are not very different; this does not allow for an easy distinction of the displacement and homolytic processes. 9 The previously determined activation parameters for the thermolysis of the methyl system under aerobic conditions 21 are generally in agreement with the BDEs obtained in this study in the presence of TEMPO. Apparently, in dilute solutions of organocobalt substrate, alkyl radical trapping by O 2 is quite effective.…”
Section: Description Of Structures (Ch 3 Ch 2 Co III Pc)supporting
confidence: 86%
See 2 more Smart Citations
“…The activation enthalpies for the methyl system are at least 6 kcal/mol higher than those determined for S N 2 methyl transfers from CH 3 CoPc, while the activation entropies for the two reactions are not very different; this does not allow for an easy distinction of the displacement and homolytic processes. 9 The previously determined activation parameters for the thermolysis of the methyl system under aerobic conditions 21 are generally in agreement with the BDEs obtained in this study in the presence of TEMPO. Apparently, in dilute solutions of organocobalt substrate, alkyl radical trapping by O 2 is quite effective.…”
Section: Description Of Structures (Ch 3 Ch 2 Co III Pc)supporting
confidence: 86%
“…For the methyl-cobalt system, apart from BDE values for the homolysis of MeCbl 18 and its popular model, CH 3 Co(DH) 2 (py), 19 and some kinetic data on CH 3 Co[TC-(4,4)], 5 there is probably only one report on the homolysis of σ-bonded methylcobalt(III) porphyrinic model 20 and one regarding the thermolysis of CH 3 Co III Pc under aerobic conditions. 21 A variety of alkylcobalt model complexes have been synthesized and extensively studied. The phthalocyanine model of MeCbl is unique in its outstanding methyl donor ability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the theoretical discussion above, one might expect square planar complexes to act as nucleophiles through the z 2 electron pair, and the addition of an apical ligand should enhance its nucleophilicity. The nucleophilic character of square planar complexes in a number of reactions has been proposed by several authors for compounds of Os(0), 16 Rh-(I), 17,18 Co(I), [19][20][21] and Pt(II). 22 Furthermore, the nucleophilicity of reduced cobaloximes has been found to depend on the nature of the axial ligand, 19 and the addition of a fifth ligand (iodide, [23][24][25][26][27] amines, 24 or acetate 25 ) to square planar complexes has been reported to enhance their nucleophilicity.…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study' it was shown that Co(1)Pc-(1-) was a good leaving group from MeCo(II1)Pc (3) [the notation is that in Ref. 1 in which the number corresponds to the formal oxidation state: 1-= Co(1)Pc-, 2 = Co(II)Pc, 3 = MeCo(III)Pc] in the solvent dimethylacetamide (DMA) with the nucleophiles I -, Br-and CN-. Cobalt complexes both as Co(1) and Co(1I) are leaving groups in cases in which the nucleophile is also a cobalt complex,273 and reactions with thiolate nucleophiles have often been studied with alkyl cobalt complexes with dimethylglyoxime and related complexing agents and also vitamin B12.…”
Section: Introductionmentioning
confidence: 99%